VPA does not enhance platinum binding to DNA in cisplatin-resistant neuroblastoma cancer cells. Issue 9 (September 2017) - Raudenska, Martina; Krejcova, Ludmila; Richtera, Lukas; Heger, Zbynek; Hrabeta, Jan; Eckschlager, Tomas; Stiborova, Marie; Adam, Vojtech; Kratochvilova, Monika; Masarik, Michal; Gumulec, Jaromir
Neuroblastoma represents a malignancy of the sympathetic nervous system characteristic by biological heterogeneity. Thus, chemotherapy exhibits only low effectivity in curing high-risk forms. Previous studies revealed the cytotoxic potential of valproate on neuroblastoma cells. Nevertheless, these studies omitted effects of hypoxia, despite its undeniable tumorigenic role. In this study, we addressed the question whether valproate promotes binding of platinum-based anti-cancer drugs (cisplatin, carboplatin and oxaliplatin) to DNA and role of hypoxia, cellular antioxidant capacity and cisplatin resistance in this process. Following parameters differed significantly when cells were exposed to treatment with platinum-based drugs: elevation of platinum content bound to DNA, elevation of total thiol content, GSH/GSSG ratio, glutathione reductase and peroxidase, superoxide dismutase and elevation of antioxidant capacity. Hypoxia caused a decrease in cytosine/adenine peak, and no changes in platinum–DNA binding properties were observed. After valproate co-treatment, oxidative stress–related parameters and cytosine/adenine peak were only elevated. The amount of platinum bound to DNA was not changed significantly. Valproate is not able to enhance platinum binding to DNA in neuroblastoma cells, neither in case of intrinsic resistance (UKF-NB-4) nor in case of acquired resistance (UKF-NB-4 CDDP ). Therefore, another mechanism different from increase in platinum binding to DNA should be considered as a synergistic effect of valproate by cisplatin treatment.